Exploration of Effective Application of Firewall Technology in Computer Network Information Security - Pan, Yurou (Journal of Theory and Practice of Management Science, 2025)
With the continuous development of information technology, computer network technology has been widely used in various fields such as people's lives, work, and learning.In the information age, the application of various information technologies has provided strong support for people's daily lives, which has also comprehensively increased the attention of various industries in China to data security.Firewall technology plays an important role in ensuring data security, so innovating and optimizing firewall technology is currently the most important research for computer network information security.Based on this, the article elaborates on the characteristics and concepts of firewall technology, and deeply analyzes the specific applications of firewall technology.